2022
DOI: 10.1007/s11356-022-23315-y
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of FeMn bimetallic ferrocene-based metal–organic frameworks to boost the catalytic efficiency for removal of organic pollutants

Abstract: A series of FeMn bimetallic ferrocene-based metal-organic frameworks (FeMn-Fc-MOFs) with various molar ratios of Fe and Mn (1:9, 2:8, 4:6, 6:4) were successfully synthesized using a simple hydrothermal synthesis method and employed as an e cient activator on persulfate (PS) activation for water decontamination. Characterizations demonstrated that Fe and Mn were smoothly introduced into ferrocene-based MOFs and various molar ratios of Fe:Mn had some in uence on crystallinity and surface structure of FeMn-Fc-MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Compared with the corresponding monometallic MOFs, the adsorption capacity of FeNi 1/60 -BDC for MB and MO was increased by a factor of 5.3 and 2.6, respectively, which was favourable for the subsequent degradation. Qu et al synthesized a series of MOFs with different Fe-Mn molar ratios (1 : 9, 2 : 8, 4 : 6 and 6 : 4) of FeMn-Fc-MOFs catalysts and selected Fe 4 Mn 6 -Fc-MOFs catalysts for the removal of Acid Orange 7 (AO7) in persulfate (PS) system [27]. Under optimal conditions, this material exhibited the removal of 92.0% for AO7 after 120 min.…”
Section: Dyesmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the corresponding monometallic MOFs, the adsorption capacity of FeNi 1/60 -BDC for MB and MO was increased by a factor of 5.3 and 2.6, respectively, which was favourable for the subsequent degradation. Qu et al synthesized a series of MOFs with different Fe-Mn molar ratios (1 : 9, 2 : 8, 4 : 6 and 6 : 4) of FeMn-Fc-MOFs catalysts and selected Fe 4 Mn 6 -Fc-MOFs catalysts for the removal of Acid Orange 7 (AO7) in persulfate (PS) system [27]. Under optimal conditions, this material exhibited the removal of 92.0% for AO7 after 120 min.…”
Section: Dyesmentioning
confidence: 99%
“…Pollutants are particles that cause environmental damage by getting into the environment naturally or through humankind [52]. Many studies have shown that BMOFs as efficient reducing agents or catalysts can remove pollutants such as ions [35][36][37][38][53][54][55][56], dyes [20][21][22][23][24][25][26][27], PPCPs [28][29][30][31][32][33][34], phenolic compounds [57,58] and microorganisms [59]. Table 1…”
Section: Removal Of Various Pollutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ferrocene has sparked widespread concern owing to its innovative double-sandwich structure and unique physical and chemical properties. For instance, several compounds containing ferrocene groups demonstrate high REDOX characteristics due to the reversible REDOX process of ferrocene groups, which can be exploited to modulate their photochemical properties and achieve REDOX switching effect. In the field of crystal engineering, for a long time, people have been eager to introduce ferrocene groups into the MOFs to explore their applications in the fields of gas separation, adsorption, catalysis, medicine, and so on. Nevertheless, proton conduction studies on ferrocene-based MOFs are rare in the literature.…”
Section: Introductionmentioning
confidence: 99%